PTH-017 Investigations, Cancer Diagnoses And Cost: A Prospective Study Of Two Week Rule Versus Non-two Week Rule Gastroenterology Referrals At A District General Hospital. (9th June 2014) - Shalabi, A; Alexakis, C; Moodie, S
Abstract : Introduction: In 2000, the UK government introduced the two-week rule (TWR) referral initiative. This was to ensure all patients with symptoms potentially indicating a diagnosis of cancer were seen by a relevant specialist within two weeks of referral by their GP. Since its initiation, very little data has indicated improved survival outcomes for patients diagnosed with cancer via this pathway. Methods: All patients referred to gastroenterology under Two Week Rule (TWR) and standard non-Two Week Rule (non-TWR) pathways were prospectively followed up for a 3 month period from date of referral. This was done covertly by the investigators to avoid influencing decision making by the clinic physicians. Data recorded included number of clinic visits, number and type of radiological/endoscopic investigations undertaken, end diagnosis and cancer diagnosis. Crude costs per patient were calculated using the hospital's unit costing database. Results: There were 52 TWR patients (mean age 72.5, male 48.1%) and 89 non-TWR patients (mean age 57.9 (p = 0.0001), male 36.0%). Reason for referral for TWR/non-TWR is shown in the table below: 76.9% of TWR patients had an endoscopic procedure compared to 62.9% of non TWR patients (p = 0.09). A similar percentage of patients in both groups underwent radiological investigation (TWR: 53.85%, non-TWR: 50.56%). More TWR patients underwent second imaging than non-TWR (9.6% vs. 6.7). 7.7% of TWR patients and 3.4% of non TWR patients had an end diagnosis of cancer, although this difference did not reach statistical significance. The mean age of the cancer patients in the TWR and non-TWR group was 70.3 years and 66.3 years respectively (although 2 of these in the non-TWR were below 65). 23.1 and 19.1% of patients had no clear diagnosis at 3 months in the TWR and non-TWR respectively. The mean cost of investigations and follow-up was significantly higher in the TWR cohort (£754.1 vs £613.1, p = 0.04). Conclusion: In our sample of patients, those referred under the TWR pathway underwent a higher burden of invasive investigation with no significant increase in cancer pick up, despite being significantly more costly. The current system possibly delays cancer diagnoses in younger patients, who are more likely to be filtered through the non-TWR pathway. Perhaps alternative referral pathways need to be considered in a bid to improve cancer diagnosis in high risk patients. Disclosure of Interest: None Declared.